A critical review of the academic entrepreneurial ecosystem in developing countries: The case of Algeria. (1st October 2019) - Chohra, Mohamed
AbstractThe objective of this article is to conduct a critical review of the literature related to the academic entrepreneurial ecosystems in developing countries in order to highlight the perspectives and to raise new questions in this area of research in these countries. The first part of this study examines the entrepreneurial context and innovation systems to determine the socio-economic and political factors that can have a negative influence on the emergence of an effective academic entrepreneurship in emerging economies. The second part explores the phenomenon of the academic entrepreneurial ecosystem in Algeria to identify the main issues and challenges that may have to be taken into consideration while promoting academic entrepreneurship in Algeria. In this study, we focus on the experience of the pharmaceutical industry as a successful model to develop effective approaches for commercializing the results of the academic research. The article also attempts to define the roles of three main actors, namely, the state, academic institutions and industry.